Genes involved in platelet aggregation and activation are downregulated during acute anaphylaxis in humans. Issue 12 (26th December 2022) - McGrath, Francesca M; Francis, Abbie; Fatovich, Daniel M; Macdonald, Stephen PJ; Arendts, Glenn; Woo, Andrew J; Bosio, Erika
Abstract: Objective: Mechanisms underlying the anaphylactic reaction in humans are not fully understood. Here, we aimed at improving our understanding of anaphylaxis by investigating gene expression changes. Methods: Microarray data set GSE69063 was analysed, describing emergency department (ED) patients with severe anaphylaxis ( n = 12), moderate anaphylaxis ( n = 6), sepsis ( n = 20) and trauma ( n = 11). Samples were taken at ED presentation (T0) and 1 h later (T1). Healthy controls were age and sex matched to ED patient groups. Gene expression changes were determined using limma, and pathway analysis applied. Differentially expressed genes were validated in an independent cohort of anaphylaxis patients ( n = 31) and matched healthy controls ( n = 10), using quantitative reverse transcription‐polymerase chain reaction. Results: Platelet aggregation was dysregulated in severe anaphylaxis at T0, but not in moderate anaphylaxis, sepsis or trauma. Dysregulation was not observed in patients who received adrenaline before T0. Seven genes ( GATA1 (adjusted P‐ value = 5.57 × 10 −4 ), TLN1 (adjusted P‐ value = 9.40 × 10 −4 ), GP1BA (adjusted P ‐value = 2.15 × 10 −2 ), SELP (adjusted P ‐value = 2.29 × 10 −2 ), MPL (adjusted P ‐value = 1.20 × 10 −2 ), F13A1 (adjusted P ‐value = 1.39 × 10 −2 ) and SPARC (adjusted P ‐value = 4.06 × 10 −2 )) were significantly downregulated in severe anaphylaxis patients who did not receive adrenaline before ED arrival, compared with healthy controls. One gene ( TLN1 (adjusted P ‐value = 1.29 × 10 −2 )) was significantly downregulated in moderate anaphylaxis patients who did not receive adrenaline before ED arrival, compared with healthy controls. Conclusion: Downregulation of genes involved in platelet aggregation and activation is a unique feature of the early anaphylactic reaction not previously reported and may be associated with reaction severity. Abstract : We have demonstrated the downregulation of genes involved in platelet aggregation during acute anaphylaxis in humans. Results suggest this response may be limited to patients who do not receive adrenaline before emergency department arrival and may be associated with reaction severity. Downregulation of platelet genes was not observed in patients with sepsis or trauma.